Uji Akurasi Kiblat Masjid di Desa Prayungan Sawoo Ponorogo Menggunakan Metode Raṣd Al-Qiblah dan Google Earth - Jauhar Wicaksono, Firdaus; Aini, Shofwatul (Program Studi Ilmu Falak UIN Sunan Ampel Surabaya, 2024)
The methods for determining the qibla direction have developed significantly over time, with many easy and practical instruments now available. These include qibla azimuth calculations, raṣd al-qiblah (qibla observation), compasses, theodolites, mizwala, Google Earth, qiblalocator, and various smartphone-based applications. This study focuses on analyzing the methods for determining the qibla direction and the level of accuracy of the qibla orientation of mosques in Prayungan Village, Sawoo, Ponorogo, based on the theories of local raṣd al-qiblah and Google Earth. This research is a field study using qualitative methods. Data collection techniques include observation and interviews. The author selected four mosques as research samples. The results reveal that two of the four sampled mosques did not use methods from the science of astronomy. Their qibla direction determination relied on village access roads and compasses with unknown levels of accuracy. Meanwhile, the other two mosques used methods based on astronomical studies, namely global raṣd al-qiblah and the theodolite. This significantly influenced the accuracy tests conducted using the local raṣd al-qiblah method and Google Earth. Two out of four mosques, including one that used the global raṣd al-qiblah method, still showed deviations in their qibla direction, while the other two mosques showed no deviation